(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This article deals with the origin of the Southwestern (SW) Palaeo-Hispanic script and its position in the history of the creation and transmission of writing systems. The supported hypothesis is that the SWscript was a full alphabet, whose signs represented vowels and consonants, not a semissyllabary. In the light of a “functionalist” perspective of the history of scripts, it would be the result of an original adaptation of the Phoenician consonantal alphabet in an Iberian setting, and wholly independent from the genesis of the Archaic Greek script (also created as a full alphabet based on the Phoenician system). This notion is supported by a review of the struc-ture and origin of the signs of the SW script. Finally, the context in which the creation of the first Paleo-Hispanic Script and the formation of the SW script (perhaps two different historical processes) may have taken place is discussed